Cognitive Fatigability is Independent of Subjective Cognitive Fatigue and Mood in Multiple Sclerosis. Issue 2 (June 2020) - Bakirtzis, Christos; Nikolaidis, Ioannis; Boziki, Marina-Kleopatra; Artemiadis, Artemios; Andravizou, Athina; Messinis, Lambros; Ioannidis, Panagiotis; Grigoriadis, Nikolaos
Abstract : Background: Sustained cognitive testing is used to detect cognitive fatigability and is often considered a substitute for subjective cognitive fatigue (CF). However, the relationship between cognitive fatigability and subjective CF in people with multiple sclerosis (PwMS) remains undetermined. Objective: To explore potential associations between fatigability induced by sustained cognitive testing and subjective CF in PwMS. Methods: We gave 120 PwMS and 60 demographically matched, healthy individuals the Beck Depression Inventory—FastScreen (BDI–FS) to measure mood and the Modified Fatigue Impact Scale to measure CF. In addition, we used the Quotient ADHD Test, a sustained attention test, to measure cognitive fatigability. We also explored potential correlations between the individuals' performance on the sustained attention test and thalamic volume using recent MRI scans. Results: Forty-one (34.2%) of the PwMS exhibited cognitive fatigability. These 41 were found to be significantly older ( P =0.006), had been diagnosed with the disease for longer ( P =0.03), had higher scores ( P <0.001) on the Expanded Disability Status Scale, and had reduced thalamic volume ( P =0.04) compared with the 79 (65.8%) PwMS not exhibiting cognitive fatigability. The PwMS exhibiting cognitive fatigability scored similarly on the BDI–FS ( P =0.21) and self-reported similar rates of CF ( P =0.62) as the PwMS not exhibiting cognitive fatigability. Conclusion: Cognitive fatigability induced by sustained cognitive testing is not an accurate clinical alternative to subjective CF. This study provides evidence to support cognitive fatigability and CF in PwMS as two distinct concepts.